Comparative characterization of putative chitin deacetylases from Phaeodactylum tricornutum and Thalassiosira pseudonana highlights the potential for distinct chitin‐based metabolic processes in diatoms. Issue 4 (15th November 2018) - Shao, Zhanru; Thomas, Yann; Hembach, Lea; Xing, Xiaohui; Duan, Delin; Moerschbacher, Bruno M.; Bulone, Vincent; Tirichine, Leila; Bowler, Chris
Summary: Chitin is generally considered to be present in centric diatoms but not in pennate species. Many aspects of chitin biosynthetic pathways have not been explored in diatoms. We retrieved chitin metabolic genes from pennate ( Phaeodactylum tricornutum ) and centric ( Thalassiosira pseudonana ) diatom genomes. Chitin deacetylase (CDA) genes from each genome ( PtCDA and TpCDA ) were overexpressed in P. tricornutum . We performed comparative analysis of their sequence structure, phylogeny, transcriptional profiles, localization and enzymatic activities. The chitin relevant proteins show complex subcellular compartmentation. PtCDA was likely acquired by horizontal gene transfer from prokaryotes, whereas TpCDA has closer relationships with sequences in Opisthokonta. Using transgenic P. tricornutum lines expressing CDA‐ green fluorescent protein ( GFP ) fusion proteins, PtCDA predominantly localizes to Golgi apparatus whereas TpCDA localizes to endoplasmic reticulum/chloroplast endoplasmic reticulum membrane. CDA‐GFP overexpression upregulated the transcription of chitin synthases and potentially enhanced the ability of chitin synthesis. Although both CDAs are active on GlcNAc5, TpCDA is more active on the highly acetylated chitin polymer DA60. We have addressed the ambiguous characters of CDAs from P . tricornutum and T . pseudonana . Differences in localization, evolution, expression and activities provide explanations underlying the greater potential of centric diatoms for chitin biosynthesis. This study paves the way for in vitro applications of novel CDAs.